Comparative Epistemology of Hadith Criticism: A Paradigmatic Analysis between the Textual Tradition and the Rational Tradition - Hikmawati, Ike; Ali Masrur; Tajul Arifin (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2025)
This study critically analyzes the epistemological foundations of hadith criticism, examining the paradigmatic conflict between the textualist Ahl al-Hadith and the rationalist Ahl al-Ra’yi/Kalam traditions. This topic is vital as it addresses the core tension between tradition and reason in Islamic thought, a debate that remains highly relevant in contemporary contexts, especially regarding hadith’s authenticity and its compatibility with modern knowledge. The research uses a qualitative, library-based comparative analysis to scrutinize the methodologies of both traditions, focusing on their respective primary sources of authority, criticism criteria, and validity standards. The research findings indicate that both paradigms possess complementary strengths and weaknesses: the textual paradigm excels in historical authenticity but lacks rational coherence, while the rational paradigm emphasizes theological consistency and universal Islamic values yet tends toward subjectivity. Both represent distinct but mutually corrective approaches to understanding prophetic truth. This study's key contribution is a proposal for a comprehensive critical epistemology that integrates the historical rigor of sanad criticism with the rational scrutiny of matn. This hybrid framework offers a balanced and accountable approach to hadith criticism, bridging the historical gap and ensuring its continued relevance for modern scholarship and believers.